2010
DOI: 10.1080/13691050903141192
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalence, silence and gender differences in church leaders’ HIV-prevention messages to young people in KwaZulu-Natal, South Africa

Abstract: A series of semi-structured interviews on HIV prevention were conducted with South African clergy with pastoral and liturgical responsibilities from the Roman Catholic Church, the Lutheran Church and the Assemblies of God. The interviews were tape-recorded, transcribed verbatim and analysed by interpretive descriptive analysis. Three themes indicative of church leaders' approach to HIV prevention among youth emerged: dilemmas in breaking the silence on HIV and AIDS; ambivalent HIV-prevention messages from chur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…In the qualitative interviews, participants revealed that cancer is stigmatized within African immigrant communities, and cancer screening is not openly discussed at church or other social gatherings. Similar findings were reported in two South African studies where clergy reported that they did not offer other health- related information such as HIV prevention and reproductive programs to their congregation due to the fear and stigma associated with these health topics ( Eriksson et al, 2010 ; Van Dyk, 2017 ). Future church-based interventions designed to improve African immigrant women's health literacy and cancer screening behaviors should also address the stigma and fatalistic beliefs surrounding cancer ( Ghebre et al, 2015 ; Raymond et al, 2014 ).…”
Section: Discussionsupporting
confidence: 86%
“…In the qualitative interviews, participants revealed that cancer is stigmatized within African immigrant communities, and cancer screening is not openly discussed at church or other social gatherings. Similar findings were reported in two South African studies where clergy reported that they did not offer other health- related information such as HIV prevention and reproductive programs to their congregation due to the fear and stigma associated with these health topics ( Eriksson et al, 2010 ; Van Dyk, 2017 ). Future church-based interventions designed to improve African immigrant women's health literacy and cancer screening behaviors should also address the stigma and fatalistic beliefs surrounding cancer ( Ghebre et al, 2015 ; Raymond et al, 2014 ).…”
Section: Discussionsupporting
confidence: 86%
“…However, although religious organizations have this influence, their involvement in HIV prevention can be complicated. In a study in South Africa documented ambivalence among church leaders about addressing HIV and inconsistent prevention messages, in part due to theology and resistance of some congregants (Eriksson, Lindmark, Axemo, Haddad, & Ahlberg, 2010). Another study conducted in three African countries suggested that churches were often silent on the issues, with some promoting traditional practices that could perpetuate the HIV epidemic (Marshall & Taylor, 2006).…”
mentioning
confidence: 99%
“…They leveraged the symbolic power of youth to project positive images of the health and future of their institutions. Researchers in other contexts have similarly documented religious leaders’ commitment to saving youth (Eriksson et al 2010) and addressing the HIV epidemic (Ansari and Gaestel 2010). They have also explored how moral ideologies may hinder HIV prevention efforts (Ansari and Gaestel 2010) and how framing HIV as the result of immoral behaviour may further increase youth vulnerability to HIV (Smith 2004).…”
Section: Discussionmentioning
confidence: 99%